Living Liver Donor With Fasciola Hepatica: First Case Report in the - Akbulut, S; Sahin, TT; Kolu, M; Isik, B; Bayindir, Y; Yilmaz, S (2021)
The major advantage of preoperative magnetic resonance cholangiopancreatography is that living liver donor candidates with complicated biliary tracts may not be exposed to unnecessary laparotomy. To the best of our knowledge, the case presented here features a condition so far not seen by the Liver Transplantation Society. A 27-year-old woman who presented to our clinic as a living liver donor candidate was evaluated but did not have a preoperative magnetic resonance cholangiopancreatography due to technical factors. After parenchymal transection, the right hepatic duct was incised just distal to the bifurcation when 8 fasciola hepatica parasites left the orifice of the remnant bile duct. The common bile duct was then irrigated, and the remnant bile duct orifice was closed, followed by a cholangiography, which showed no suspicious lesions in the biliary tracts. In addition, no suspicious lesions were identified during the postoperative cholangiography of the graft implanted in the recipient. The donor and recipient had postoperative enzyme-linked immunosorbent assay immunoglobulin G antibody titers of 12 and 4 U/mL (cutoff value = 10) for fasciola hepatica, respectively. Both the recipient and the donor received 2 doses of triclabendazole (10 mg/kg) during the postoperative period. C1 [Akbulut, Sami; Sahin, Tevfik Tolga; Isik, Burak; Yilmaz, Sezai] Inonu Univ, Dept Surg, Fac Med, Malatya, Turkey. [Akbulut, Sami; Sahin, Tevfik Tolga; Isik, Burak; Yilmaz, Sezai] Inonu Univ, Liver Transplant Inst, Fac Med, Malatya, Turkey. [Kolu, Mehmet] Inonu Univ, Fac Med, Dept Radiol, Malatya, Turkey. [Bayindir, Yasar] Inonu Univ, Fac Med, Infect Dis & Clin Microbiol, Malatya, Turkey.